Meningkatkan Kualitas Hafalan Al-Qur’an Melalui Ajang Perlombaan Tahfiz Al-Qur’an Se-Kota Payakumbuh - Solihati, Septia; Hidayat, Tatang; Fairuzana, Nadhira; Salsabila, Syifa; Januarti, Putri; Hashifah, Nabilah; Putri, Dilah Hardiyana; Azzahra, Giana (Zad Al-Ummah: Jurnal Pengabdian Masyarakat, 2024)
Tahfiz Al-Qur'an is an effort to maintain, memorize, maintain and preserve the Qur'an revealed to the Prophet Muhammad SAW. Islamic boarding schools that are mushrooming in Indonesia will be incomplete without this activity. Even in non-boarding schools, Qur'anic tahfiz is one of the extracurriculars. This shows how much attention Muslims pay in memorizing the Qur'an. To  test and improve the quality of memorization of the Qur'an, it is necessary to hold a Qur'an tahfiz competition. This journal discusses the Qur'an tahfiz competition as a place to improve the quality of memorization. The method used is observation. The results showed that the Qur'an tahfiz competition can spur the enthusiasm of Qur'an memorizers, train competitive spirits and establish ukhuwah Islamiyah among fellow Qur'an memorizers.